The Role of Cooperative Society for Marketing Agricultural Products in Bangladesh (Global Journal of Management and Business Research, 2015)
Bangladesh is a developing country and agriculture is the main largest sector of the economy. About 80% people are directly or indirectly depended on the agriculture for their livelihood. This sector Contributes 35.47% to the Gross Domestic Product (GDP) and this sector provides about 63% employment for the workforce. Most of the farmers are illiterate and for that reason they do not have the ability to sell their products to the final consumers. Consequently, middlemen are playing marketing role and due to this reason, farmer are not getting fair price for their products. Ministry of local Government & Cooperative Society can play vital role to bring forming within the framework of Cooperative Society and can minimize the role of middlemen of marketing agricultural products of Bangladesh.
Keywords: Cooperative Society; Cooperative Marketing; Middlemen; Philosophy; Gross Domestic Product (GDP); RDCD